2016
DOI: 10.1371/journal.pone.0146340
|View full text |Cite
|
Sign up to set email alerts
|

Access to Bacteriologic-Based Diagnosis in Smear Positive Retreatment Tuberculosis Patients in Rural China: A Cross-Sectional Study in Three Geographic Varied Provinces

Abstract: ObjectiveTo determine factors influencing the utilization and accessibility to bacteriologic-based tuberculosis (TB) diagnosis among sputum smear positive (SS+) retreatment TB patients, and to develop strategies for improving the case detection rate of MDR-TB in rural China.Study Design and SettingA cross-sectional study of SS+ TB retreatment patients was conducted in eight counties from three provinces with different implementation period and strategy of MDR-TB program in China. Demographic and socioeconomic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…However, we observed a substantial decrease in correct responses among participants in Jiangxi province a year after training, while the correct responses improved among participants in Liaoning province. The decline observed in Jiangxi province 1 year after the training may be because HCPs in Jiangxi province had fewer opportunities to perform MDR-TB laboratory diagnostic tests in their daily jobs than those in Liaoning province; a study has found that the availability of diagnostic tests for drug-resistant TB varies among different geographical regions in China 18…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we observed a substantial decrease in correct responses among participants in Jiangxi province a year after training, while the correct responses improved among participants in Liaoning province. The decline observed in Jiangxi province 1 year after the training may be because HCPs in Jiangxi province had fewer opportunities to perform MDR-TB laboratory diagnostic tests in their daily jobs than those in Liaoning province; a study has found that the availability of diagnostic tests for drug-resistant TB varies among different geographical regions in China 18…”
Section: Discussionmentioning
confidence: 99%
“…A major barrier to scaling up the programme nationwide is ensuring that clinical staff at peripheral health centres are appropriately trained in providing quality MDR-TB services—including implementing new diagnostic protocols—according to the national guidelines. The China CDC is particularly focused on improving early detection on MDR-TB using the new diagnostic protocols as the MDR-TB case detection rate in China was only 7.7% in 2014,15 and one of the major factors for the low detection rate is lack of trained HCPs 16–18. Health policymakers in the China CDC and CMA are therefore considering investments in countrywide training programmes to ensure standardised programmatic management of MDR-TB.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, studying DR-TB, specifically MDR-TB, in rural areas is of key importance for monitoring and controlling TB in China. Previous studies on TB in rural areas of China have been limited by a short time span and small sample size of culture-positive TB cases (Zhou et al, 2016;Li et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Although several studies reported the difficulties in accessing to MDR-TB diagnosis [7,12], few have directly illustrated what patients experienced after they were diagnosed as MDR-TB, for instance, what kind of treatment they received and how the quality of care influenced their treatment outcomes. MDR-TB patients should be provided with a recommended regimen containing at least five effective second-line anti-TB drugs in a 6-month intensive phase and at least four drugs in an 18-month consolidation phase according to the national MDR-TB prevention and control program [13], or a standardized shorter MDR-TB regimen as recommended recently by the WHO [14].…”
Section: Introductionmentioning
confidence: 99%
“…As the WHO reported in 2018, the MDR-TB detection rate was only 22.8% in China coupled with a treatment coverage of 13.6% [ 2 ]. Poor accessibility to drug susceptibility testing (DST) especially in rural areas [ 7 ], long waiting time for conventional DST results [ 8 ] and incomplete high-risk screening strategy for MDR-TB [ 9 ] might explain the low detection rate of MDR-TB in China; while delayed DST, unaffordable treatment cost, drug-induced adverse effects and fragile supply chain of second-line drugs could be the main reasons for the low treatment coverage [ 5 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%